Maren Pills Improve Constipation via Regulating AQP3 and NF-κB Signaling Pathway in Slow Transit Constipation In Vitro and In Vivo. (23rd July 2020) - Zhan, Yu; Tang, Xuegui; Xu, Hong; Tang, Shiyu
Abstract : Background . Maren pills have been used to treat constipation. Aquaporin 3 (AQP3) plays a vital role in regulating water transfer in the colon. It has been reported that the downregulation of AQP3 can regulate liquid water metabolism and intestinal permeability in irritable bowel syndrome (IBS) rats' colon via NF- κ B pathway. In this study, we investigated whether the laxative effect of Maren pills is associated with the regulation of AQP3 and NF- κ B signaling pathway in the colon. Methods . The compound diphenoxylate suspension-induced STC rats received Maren pills intragastrically for 1 consecutive week to evaluate the laxative effect of Maren pills involving the regulation of AQP3 and NF- κ B signaling pathway. Moreover, human intestinal epithelial cells (HT-29) were treated with drug serum to obtain in vitro data. Results . Our results revealed that treatment with Maren pills increased the stool number, moisture content of feces, and intestinal transit rate in a dose-dependent manner. Maren pills significantly increased the AQP3, fibrosis transmembrane conductance regulator (CFTR), and protein kinase A (PKA) proteins in the colon of rats and in HT-29 cells. Mechanistically, Maren pills obviously inhibited the activation of NF- κ B pathway in the colon of rats and in HT-29 cells. Conclusion . These results suggest that the laxative effect of Maren pills is associated with the increased expression of AQP3 by downregulating NF- κ B signal pathway.